The cooperative experience of cogon farmers : food security for small farmers - Agaton, Sheldon Ives; Cajipo, Sarah; Lagdamen, Daisy; Españo, Sherwin; Santos, Kay Bathala; Dula, Rosalita (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cooperativism is a method introduced by people in a society to neutralize the competitive prices of goods from among business sectors. It is a way for people to come together, put up their goods and services as one, and with the end in view of benefiting from their products. The purpose of this study is to appraise the fundamental function of cooperativism and how it can assist and sustain small farmers in their aim for food security. This work utilized hermeneutical phenomenology in understanding the lived experiences of small farmers in Barangay Cogon, Tanauan, Leyte, Philippines from the establishment of their cooperative, its operation, and its eventual success in giving them food security in the process. The results indicate that farmers were hesitant in establishing a cooperative because of the groundwork that accompanies it. But with the aid of the faculty members of the Eastern Visayas State University, the farmers underwent education on the nature of cooperativism. From there, the faculty members allowed the farmers to cultivate discipline, sustenance, and business integrity while operating the cooperative. Constant monitoring from the faculty members over the farmers was necessary to ensure that the cooperative was consistently maintained thereby achieving stability and eventual food security. For years now, the cooperative has helped its members substantially. Coincidentally, the occurrence of the covid-19 virus has made significant changes or damages to human life and properties, but this cooperative gave hope and food sustenance to its members. This study hopes that the effort of the initiators coupled with the cooperation and effort of the cooperative members exemplify the need to proliferate cooperativism in every society especially among poor farmers.